Calidad del agua en piscinas de Geomembrana y suelo para la cría de chame (Dormitator latifrons) ubicadas en Área Agropecuaria, ESPAM MFL. - Chila Zambrano, Gustavo Andrés (2018)
The research work was carried out in the polytechnic campus in the agricultural area, located in the Limón sector of the city of Calceta, province of Manabí. The main objective of this research work was to evaluate the influence of chame (Dormitator latifrons) in the water quality of the pools located in the livestock race of ESPAM MFL. For its effect, maintenance tasks were given to the pools, since a pool with soil and another without soil was used, after that, the fry were planted in a study in floating cages, which were acquired in the city of San Vicente from the province of Manabí; later, samplings were made for their respective analysis. We proceeded to perform physical and chemical analyzes to the water of the pool with soil and the pool without soil, obtaining as a result for both pools a pH of 8.3; while in the other parameters (Turbidity, dissolved oxygen, temperature, color, conductivity, hardness, chlorides and sulphates) there was a significant variation. Finally, the comparison of the results obtained with the Water Quality criteria for livestock use, established in Annex 1 of the Unified Legislation of Secondary Legislation of the Ministry of the Environment: Standard of Environmental Quality and Discharge of Effluents to the Water Resource.